The forgotten spine score: study protocol for a novel patient-centered outcome measure in lumbar spine fusion surgery - Ambrosio, Luca; Schol, Jordy; Otani, Yuto; Petrucci, Giorgia; de Rinaldis, Elisabetta; Tamagawa, Shota; Russo, Fabrizio; Papalia, Rocco; Sakai, Daisuke; Vadalà, Gianluca; Denaro, Vincenzo (Frontiers in Surgery, 2025)
Lumbar spine fusion (LSF) surgeries have increased due to the rising prevalence of degenerative spine disorders and advancements in surgical techniques. However, the success of these procedures should be evaluated from the patient's perspective, emphasizing the need for effective patient-reported outcome measures (PROMs). Existing PROMs often focus on symptoms and lack specific validation for surgical patients undergoing LSF. Inspired by the Forgotten Joint Score used in joint replacement surgery, here we introduce the Forgotten Spine Score (FSS), a new patient-centered PROM designed to assess the extent to which patients “forget” about the operated spinal segment(s) in their daily lives. This study protocol outlines our approach to develop and validate the FSS as a reliable tool for evaluating outcomes in LSF patients, focusing on their perception of surgery's impact on daily life and well-being. This multi-institutional cross-sectional study will involve a pilot phase to refine the newly designed 18-item FSS survey in Italian and Japanese, followed by a validation phase to assess the adjusted survey in the respective populations. Eligible participants will include adults who have undergone LSF for degenerative disorders at varying follow-up times. The FSS will be administered alongside the Oswestry Disability Index (ODI). Statistical analyses will assess internal consistency, reliability and validity, with significance set at p < 0.05. The survey will be assessed based on its correlation with the ODI, potential for enhanced sensitivity, and overall appreciation among LSF patients. By improving our understanding of patient-centered outcomes, the FSS has the potential to inform clinical decision-making and patient care.